Long-term effectiveness and safety of methotrexate-tacrolimus combination therapy versus methotrexate monotherapy in reducing rheumatoid arthritis flares after TNF inhibitor discontinuation: a retrospective cohort study - Taio Naniwa; Mikiko Kajiura (BMC Rheumatology)
Abstract Background This study evaluates the long-term effectiveness and safety of methotrexate-tacrolimus combination therapy compared to methotrexate monotherapy in maintaining successful tumor necrosis factor (TNF) inhibitor discontinuation in rheumatoid arthritis (RA) patients. Methods We retrospectively analyzed consecutive RA patients who discontinued TNF inhibitors after achieving disease control by October 2022 and received either methotrexate monotherapy or methotrexate-tacrolimus combination therapy for up to 10 years. Per-observation time-to-event analyses assessed treatment failure, treatment intensification, first disease flare, and irreversible functional deterioration. Mixed-effects Cox models, time-dependent Cox models without random effects, and Kaplan-Meier estimates with inverse probability weighting were applied. Safety assessment included treatment-limiting adverse events and renal function trends. Results A total of 147 treatment lines (96 methotrexate monotherapy and 51 combination therapy) in 116 patients were analyzed. The combination therapy significantly reduced treatment failure (hazard ratio [HR], 0.42; 95% confidence interval [CI], 0.24–0.72), treatment intensification with the index drugs (HR, 0.38; 95% CI, 0.22–0.67) and with biologics or Janus kinase inhibitors (HR, 0.39; 95% CI, 0.22–0.71), and first flare (HR, 0.55; 95%CI 0.36–0.84), with consistent findings across models. The benefit was most pronounced in patients with prior flares during methotrexate monotherapy after TNF inhibitor discontinuation, with HRs as low as 0.04–0.12 across outcomes. No significant differences in treatment-limiting adverse events were observed. The annual increase in serum creatinine for tacrolimus users was 0.0032 mg/dL, suggesting minimal long-term renal impact. Conclusions Methotrexate-tacrolimus combination therapy significantly reduces relapse risk following TNF inhibitor discontinuation without compromising safety, offering a potentially sustainable treatment alternative after achieving remission with TNF inhibitor therapy.